Feasibility and safety study of 22-gauge endoscopic ultrasound (EUS) needles for portal vein sampling in a swine model - Park, Kenneth; Lew, Daniel; Chapman, Christopher; Wachsman, Ashley; Bloom, Matthew; Bancila, Liiana; Perry, Rachel; Wang, Qiang; Jamil, Laith; Pandol, Stephen; Lo, Simon (Endoscopy International Open, 2020)
Background and study aims Endoscopic ultrasound (EUS) has been used for portal vein sampling in patients with pancreaticobiliary cancers for enumerating circulating tumor cells but is not yet a standard procedure. Further evaluation is needed to refine the methodology. Therefore, we evaluated the feasibility and safety of 19-gauge (19G) versus a 22-gauge (22 G) EUS fine-needle aspiration needles for portal vein sampling in a swine model. Methods Celiotomy was performed on two farm pigs. Portal vein sampling occurred transhepatically. We compared 19 G and 22 G needles coated interiorly with saline, heparin or ethylenediaminetetraacetic acid (EDTA). Small- (10 mL) and large- (25 mL) volume blood collections were evaluated. Two different collection methods were tested: direct-to-vial and suction syringe. A bleeding risk trial for saline-coated 19 G and 22 G needles was performed by puncturing the portal vein 20 times. Persistent bleeding after 3 minutes was considered significant. Results All small-volume collection trials were successful except for 22 G saline-coated needles with direct-to-vial method. All large-volume collection trials were successful when using suction syringe; direct-to-vial method for both 19 G and 22 G needles were unsuccessful. Collection times were shorter for 19 G vs. 22 G needles for both small and large-volume collections (P < 0.05). Collection times for saline-coated 22 G needles were longer compared to heparin/EDTA-coated (P < 0.05). Bleeding occurred in 10 % punctures with 19 G needles compared to 0 % with 22 G needles. Conclusion The results of this animal study demonstrate the feasibility and the safety of using 22 G needles for portal vein sampling and can form the basis for a pilot study in patients.